Kajian : Pola Pengeluaran Pangan Rumahtangga Petani Padi Sawah di Kabupaten Banjar Kalimantan Selatan - Sari Novita; Fardianah Mukhyar (Universitas Lambung Mangkurat, 2011)
The purpose of the research was to analyze the food expenditure pattern of paddy farmer’s household in Banjar Regency. The study was conducted in June until November 2009 in two subdistricts of Banjar Regency of South Kalimantan Province. Two villages were chosen from each subdistrict namely Kayu Bawang and Melintang (Gambut Subdistrict), and Penggalaman and Keliling Benteng Ulu (Martapura Barat Subdistrict). The village choosing was based on the poverty level (Purposive Sampling). The research was sample survey research by using cross section data. The samples were taken randomly. The analysis methods used were descriptive using tables. The result indicated that in Banjar Regency, the rate expenditure for food was higher than for non-food. The rate of food expenditure was Rp 6,818.82/capita/day (52.30%), while for non-food was Rp 6,219.27/capita/day (47.70%). There were 32 poor farmer household (35.56%) and 58 rich farmer household (64.44%). The result also indicated that the percentage of food expenditure was still dominated by the staple foods (30,54%). The activity of the food expenditure pattern development should be put in priority through the diversification development as the effort to increase the buying capacity.